INNOVATION IN A PRODUCER GROUP FOCUSED ON MILK PRODUCTION OF THE SILESIAN PROVINCE - Szelag-Sikora, Anna; Komorowska, Monika; Ovcharuk, Oleg; Grodek-Szostak, Zofia; Stuglik, Joanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the work was to analyse the level of innovation in the group of milk producers and production efficiency. The work covered its scope with the producer group established in 2010, which brings together six producers of cow's milk. The farms are run based on a conventional production system. The source data used in the analysis covers the years 2010-2017. The analysis covered the number of implemented innovations, the type of innovation and the level of expenditures borne by producers for introducing the innovations. Based on the results obtained, the relative benefits achieved by the producer group resulting from the introduction of innovative solutions were determined.